Could Neurolecturing Address the Limitations of Live and Recorded Lectures? - David Gamez (Humana.Mente: Journal of Philosophical Studies, 2018)
Lectures are a common teaching method in higher education. However, they have many serious limitations, including boredom, attendance, short attention span, low knowledge transmission and the passivity of students. This paper suggests how a combination of electroencephalography (EEG) and eye-tracking technology could address some of these limitations – an approach that I have called neurolecturing. Neurolecturing could measure students’ attention, learning and cognitive load and provide real time feedback to students and lecturers. It could also play a role in the flipped classroom and artificial intelligence tutoring.